Variation in fuelwood properties of five tree/shrub species in the Sahelian and Sudanian ecozones of Mali: relationships with rainfall, regions, land-use and soil types - Sotelo Montes, Carmen; Weber, John C.; Silva, D.A.; Muñiz, G.I.B.; García, R.A. (Brown Walker Press, 2012)
We investigated variation in age-adjusted fuelwood properties of Balanites aegyptiaca, Combretum glutinosum, Guiera senegalensis, Piliostigma reticulatum and Ziziphus mauritiana along latitudinal transects in five regions extending from eastern to western Mali. The objectives were to determine if fuelwood properties differed among regions, land-use and soil types and/or varied with latitude, longitude, elevation and mean annual rainfall in the Sahelian and Sudanian ecozones of Mali. Based on the results, we recommend fuelwood production in all regions for G. senegalensis, in drier regions for B. aegyptiaca and C. glutinosum, in more humid regions for Z. mauritiana, on rocky soils for all species, in woodlands for G. senegalensis but in parklands for Z. mauritiana. Fuelwood production of P. reticulatum is not recommended. Furthermore, we recommend (a) using seed of B. aegyptiaca, C. glutinosum and G. senegalensis from drier locations to establish fuelwood plantations, and (b) conducting similar research on fuelwood species throughout the region in order to make regional recommendations for fuelwood plantations in a changing climate.